Frequency, pattern and predictors of cognitive impairments in patients with Parkinson’s disease using the Community Screening Instrument for Dementia - Ogbimi, Ewere Marie; Akemokwe, Fatai Momodu; Ogunrin, Olubunmi (Frontiers in Human Neuroscience, 2023)
Background Parkinson’s disease (PD) is a chronic neurodegenerative disorder complicated by cognitive dysfunctions which are associated with increased caregiver burden, pressure on community health facilities, and mortality in affected patients. Most of the data concerning cognitive dysfunctions in PD are from studies conducted in Europe and North America, but there is a paucity of data from Sub-Saharan Africa. Objective The objective of this study is to determine the frequency, pattern, and predictors of cognitive impairments among patients with Parkinson’s disease. Materials and methods This was a cross-sectional case-control study carried out at a tertiary health facility in South-south Nigeria. Participants with PD were consecutively recruited from the neurology outpatient clinics. Demographic and disease-specific data were obtained with the use of a pre-tested questionnaire. The cognitive performance of thirty patients with PD was compared with thirty demographically matched controls using the Community Screening Instrument for Dementia (CSID). CSID was already validated among Nigerians. Results The frequency of cognitive impairment using the CSID was 50% for PD patients (3.3% for controls). Poor cognitive performance was observed across several cognitive domains including language, executive dysfunction, psychomotor speed, and constructional apraxia among PD patients. The independent predictors of the overall cognitive impairment in patients with PD using logistic regression analysis include recall deficiency (p=0.007), impairment with naming (p=0.044), apraxia (p=0.003), Hoen&Yahr staging (p=0.046), UPDRS score (p=0.015) and age at presentation (p=0.014). Conclusion Cognitive impairments occur more frequently in patients with PD compared to controls. This study also demonstrated the predictive role of the severity of disease based on Hoehn &Yahr staging and UPDRS score, and the presence of recall deficiency, poor naming ability, and apraxia.